Integrating evidence and experience - How a new approach to monitoring and evaluation can make sense of complex projects - Gregorowski, Robbie; Craig, Zand; Nguyen, Ly; Mull, Savi (2022)
How a new approach to monitoring and evaluation can make sense of comp lex projects Building the foundation for results, sense-making and lea rning ‘Demonstrating real world impact can be an elusive holy grail fo r most NGO …